Comparison of fatty acids profile and antioxidant enzyme level of cladoceran Moina brachiata (jurine, 1820) from freshwater bodies of Chennai - Jeyam. M, Gomathi; Ravichandran, Ramanibai (International Journal of Scientific World, 2017)
Omega-3 family (Ï‰-3) of polyunsaturated fatty acids (PUFA) was considered as an important biochemical for the physiological function of all trophic level animals. In this study, we demonstrated the effect of algal diet on fatty acids composition (FA), antioxidant enzymes and DNA damage of Moina brachiata from Adyar River and Kolavoi Lake. 8 different fatty acids were identified in M. brachiata through GC-MS analysis and we noticed two PUFA (Eicosapentaenoic acid, EPA 20:5 (Ï‰-3); Linoleic acid 18:2 (Ï‰-6)). The dietary fatty acid accumulation and bioconversion capacity of M. brachiata have differed in two lakes fed with algal diet. The high amount of Ï‰-3 PUFA was observed in M. brachiata fed with Scenedesmus sp. in Kolavoi Lake (35.84%) followed by Adyar River (33.78%). PUFA content was significantly declined in wild M. brachiata of Adyar River (17.44%) followed by Kolavoi lake (25.78%). On the other hand, high level of Malondialdehyde (MDA) and decreasing level of key antioxidant enzymes likes Superoxide dismutase (SOD), Catalase (CAT), Glutathione peroxidase (GSH) and DNA damage were observed in wild M. brachiata of Adyar River. Hence, the algal diet could enhance the level of antioxidant enzyme activity by decreasing the level of MDA and it does not show DNA damage on M. brachiata. Overall, the results obtained in this study explored that Scenedesmus sp., has the ability to enhance the PUFA content, antioxidant enzyme activity and prevent the DNA damage in M. brachiata which was declined in the wild animal due to the environmental stress conditions.